2020
DOI: 10.1186/s12937-020-00598-w
|View full text |Cite
|
Sign up to set email alerts
|

The use of Lactobacillus plantarum 299v (DSM 9843) in cancer patients receiving home enteral nutrition – study protocol for a randomized, double-blind, and placebo-controlled trial

Abstract: Background Nutritional treatment is one of the most important components of multidisciplinary anti-cancer therapy. Home enteral nutrition is considered as a safe procedure, however, it may be associated with the risk of side effects, such as nausea, vomiting, abdominal pain, and diarrhoea. It is uncertain whether diarrhoea is the result of the enteral formula administration or gut dysbiosis. One of the methods which may be used to alter the composition of gut microbiota is the administration of a probiotic str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Following these criteria, a substantial body of evidence confirmed the successful use of diverse human probiotic Lpb. plantarum strains as a dietary intervention to prevent and/or ameliorate some widespread diseases, especially acute and chronic GI infections (i.e., C. difficile and H. pylori infections) [ 99 , 175 ], gut inflammatory syndrome (i.e., Irritable Bowel Disease (IBD) and Ulcerative Colitis) [ 176 , 177 ] cardiovascular diseases [ 178 ], hypercholesterolaemia and obesity [ 179 , 180 ], diabetes [ 181 ], gynaecological diseases [ 182 ] as well as colon cancer [ 183 ] and cognitive impairments [ 184 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Following these criteria, a substantial body of evidence confirmed the successful use of diverse human probiotic Lpb. plantarum strains as a dietary intervention to prevent and/or ameliorate some widespread diseases, especially acute and chronic GI infections (i.e., C. difficile and H. pylori infections) [ 99 , 175 ], gut inflammatory syndrome (i.e., Irritable Bowel Disease (IBD) and Ulcerative Colitis) [ 176 , 177 ] cardiovascular diseases [ 178 ], hypercholesterolaemia and obesity [ 179 , 180 ], diabetes [ 181 ], gynaecological diseases [ 182 ] as well as colon cancer [ 183 ] and cognitive impairments [ 184 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“… 26 , 27 Kazmierczak-Siedlecka et al found that lactobacillus (extracted from pickle) supplementation could improve exercise performance in a dose-dependent manner and significantly increases muscle mass in healthy people, and reduce the muscle loss in cancer patients. 28 These experiments suggest that lactobacillus may become a biological agent for improving physiological function. 29 …”
Section: The Potential Role Of Gut Microbiota In Gut-muscle Axismentioning
confidence: 98%
“…Supplementing the corresponding microbiota is also beneficial to fight the disease. 28 , 30 Therefore, probiotics are closely related to muscle strength and function and muscle mass. Although there is limited understanding of probiotics’ mechanism on muscle strength and quality benefits at this stage, it is clear that gut microbiota is linked to muscles through endocrine, substance and energy metabolism, immunity and inflammation.…”
Section: The Potential Role Of Gut Microbiota In Gut-muscle Axismentioning
confidence: 99%
“…L. plantarum 299v, which was originally isolated from human intestine, is characterized by multiple properties [ 35 , 36 , 37 ], e.g., it is able to survive in a wide range of pH, demonstrating a high tolerance to acidic conditions in the stomach and the more basic pHs in duodenum [ 38 ]. L. plantarum 299v also acts against potentially pathogens (e.g., Enterococcus faecalis , Bacillus cereus , Yersinia enterocolitica , Clostridium difficile , and Escherichia coli ) and inhibits their growth in the gut [ 38 ].…”
Section: The Probiotics and The Interactions With Immune Systemmentioning
confidence: 99%